Análise florística e biogeográfica das savanas da Caatinga - Nepomuceno, Izaíra Vasconcelos (2021)
The savanic vegetation of the Cerrado is dominant in central Brazil. But we also find enclaves of savannas within the Caatinga Domain along the coast of Caatinga and in highlands like the Chapada Diamantina and Chapada do Araripe or in smaller patches in Bahia, Ceará, Piuaí, Paraíba and Rio Grande do Norte states. The flora of these patches of savannas in Caatinga was considered impoverished in relation to cerrado areas of central Brazil and have species from both typical cerrado and species from the surrounding Caatinga vegetation. This study investigates the influence of the Caatinga flora in these savanna enclaves and how floristically similar they are to the cerrados of central Brazil. We made floristic studies in savanna enclaves within the Caatinga in Ceará. We also organized a database with floristic lists of sites from Cerrados of centra Brazil, savanna enclaves in Caatinga, caatinga stricto sensu, Amazonian savannas and campos rupestres to compare the floristic relationship of these caating savannas with other vegetation types using multivariate analyses. We recorded in database 6.666 species. We show that savanna enclaves in Caatinga have a larger proportion of terophytes than hemicryptophytes and phanerophytes, which are most frequent the life-forms in the central cerrados. The flora in these Caatinga savannas is composed by species from both the caatinga sensu stricto vegetation, like Combretum leprosum and Anadenathera columbrina, and species from the cerrado sensu stricto, such as Qualea grandiflora and Curatella americana. The multivariate analyses showed that there are at least three floristic groups of Caatinga savannas: those located on higher altitudes, like Chapada do Araripe and Chapada Diamantina, are floristically closer to the cerrados sensu stricto of central Brazil; while those in drier sites, that are in greater contact with the Caatinga, have stronger relationships with the caatinga vegetation. Sites with cerradão phytophysiognomies formed a group with other sites with the same phytophysiognomie, even when geographically distant. We conclude that savannas located in different Phytogeographical Domains do not constitute a cohesive floristic group, and are different in species composition, even considering that they share a number of widespread species typical of the cerrado sensu stricto of central Brazil.